Citizen or consumer? Reconsidering energy citizenship. Issue 2 (3rd March 2020) - Lennon, Breffní; Dunphy, Niall; Gaffney, Christine; Revez, Alexandra; Mullally, Gerard; O'Connor, Paul
ABSTRACT: The transition to more sustainable energy systems has set about redefining the social roles and responsibilities of citizens. Implicit in this are expectations around participation, though the precise contours of what this might mean remain open. Debates around the energy transition have been skewed towards a normative construct of what it means to be a 'good citizen', the parameters for which are shaped by predetermined visions of statist and/or market-driven determinations of the energy systems of the future. This article argues that concepts such as 'energy citizen' are co-opted to reflect popular neoliberal discourses, and ignore crucial questions of unequal agency and access to resources. Paradoxically, official discourses that push responsibility for the energy transition onto the 'citizen-as-consumer' effectively remove agency from citizens, leaving them largely disconnected and disempowered. Consequently, energy citizenship needs to be reconceptualised to incorporate more collective and inclusive contexts for action. Considering how much energy consumption occurs in (traditionally female) domestic spheres, do conventional notions of citizenship (especially with regards to its associated rights and duties) need to be recalibrated in order for the concept to be usefully applied to the energy transition?